MAKNA KEBANGKITAN YESUS BERDASARKAN SURAT-SURAT PAULUS - Resa Junias; Dorce Sondopen (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2020)
Abstract: Basically, Jesus was willing to offer himself to come down to earth to teach the gospel to every human being and was willing to be tortured, crucified, and died to atone for human sins. The purpose of this research is to answer the question: What does God want about His resurrection? How important is the resurrection of Jesus for the lives of believers? What effect will the resurrection of Jesus Christ have on the lives of believers? The answer was: (1) His bodily resurrection and eternity. Everything is possible because Christ, after He rose from the dead, did not die again, in other words, He lives and continues to live. The resurrection of Christ happened a transfer of power, Christ went from being ruled by death to being ruler over death. (2) Without the resurrection, Christian faith is not possible. His disciples are only symbols of defeat and destruction. Without the resurrection, Jesus' position as Messiah and King would be inexplicable. Without the resurrection, the outpouring of the Holy Spirit would leave an inexplicable mystery. Without the resurrection, the source of the disciples' testimony was lost. (3) The impact of the resurrection of Jesus Christ for the lives of believers is that as long as man is in God, whatever he does, all his efforts in God, will receive a reward or reward from God. Abstrak: Pada dasarnya Yesus rela mempersembahkan diri-Nya untuk turun ke bumi guna mengajarkan injil bagi setiap manusia dan rela disiksa, serta disalibkan, dan mati bagi menebus dosa manusia. Tujuan penelitian ini menjawab pertanyaan: Apakah yang Tuhan inginkan tentang kebangkitan-Nya? Bagaimana pentingnya kebangkitan Yesus untuk kehidupan orang percaya? Apa dampak kebangkitan Yesus Kristus bagi kehidupan orang percaya? Jawabnya adalah: (1) Kebangkitan tubuhnya dan berlanjut dalam kekekalan. Semuanya dapat terjadi karena Kristus, sesudah Ia bangkit dari antara orang mati, tidak mati lagi, dengan kata lain, Ia hidup dan terus hidup. Kebangkitan Kristus terjadi peralihan kekuasaan, Kristus beralih dari dikuasai oleh maut menjadi penguasa atas maut. (2) Tanpa kebangkitan, iman Kristen tidak mungkin muncul. Murid-murid-Nya hanyalah simbol kekalahan dan kehancuran. Tanpa kebangkitan, posisi Yesus sebagai Mesias dan Raja tidak akan terjelaskan.  Tanpa kebangkitan, pencurahan Roh Kudus akan meninggalkan misteri yang tidak dapat dijelaskan. Tanpa kebangkitan, sumber kesaksian murid-murid hilang. (3) Dampak kebangkitan Yesus Kristus bagi kehidupan orang percaya adalah  selama manusia ada di dalam Tuhan, apapun yang ia kerjakan, semua jerih payahnya dalam Tuhan, akan mendapat balasan atau upah dari Tuhan.